Bottle-feeding techniques for children with cleft lip and palate experiencing feeding difficulties - Shingo Ueki; Ayaka Fujita; Yukari Kumagai; Yumi Hirai; Eri Tashiro; Junko Miyata (International Journal of Nursing Sciences, 2023)
Objective: This study aimed to identify clinical bottle-feeding techniques practiced by nurses for children with cleft lip and palate experiencing feeding difficulties. Methods: A qualitative descriptive design was used. Five anonymous questionnaires were distributed to each hospital, and 1,109 hospitals with obstetrics, neonatology, or pediatric dentistry wards in Japan were enrolled in the survey between December 2021 and January 2022. Participants were nurses working for over 5 years providing nursing care for children with cleft lip and palate. The questionnaire comprised open-ended questions about the feeding techniques across four dimensions: preparation before bottle-feeding, nipple insertion methods, sucking assistance, and criteria for stopping bottle-feeding. The qualitative data obtained were categorized according to meaning similarity and analyzed. Results: A total of 410 valid responses were obtained. The findings regarding the feeding techniques in each dimension were as follows: seven categories (e.g., improving child’s mouth movement, keeping child’s breath calm), 27 sub-categories in preparation before bottle-feeding; four categories (e.g., closing the cleft using the nipple to create negative pressure in oral cavity, inserting the nipple to not touch the cleft), 11 sub-categories in nipple insertion methods; five categories (e.g., facilitating awakening, creating negative pressure in oral cavity), 13 sub-categories in sucking assistance; and four categories (e.g., reduced awakening level, worsening vital signs), 16 sub-categories in criteria for stopping bottle-feeding. Most participants responded that they would like to learn bottle-feeding techniques for children with cleft lip and palate who have feeding difficulties. Conclusion: Many bottle-feeding techniques were identified to address disease-characterized conditions. However, the techniques were found to be conflicting: some inserted the nipple to close the cleft to create negative pressure in the child’s oral cavity, while others inserted it without touching the cleft to prevent ulceration on the nasal septum. Although these techniques were used by nurses, the effectiveness of the methods has not been assessed. Future intervention studies are needed to determine each technique’s benefit or potential harm.